39. Central sensitization as the mechanism underlying pain in joint hypermobility syndrome/Ehlers–Danlos syndrome, hypermobility type. Issue 12 (December 2016) - Pepe, A.; Leone, C.; Di Stefano, G.; Celletti, C.; Baron, R.; Castori, M.; Di Franco, M.; La Cesa, S.; Cruccu, G.; Truini, A.; Camerota, F.
Abstract : Patients with joint hypermobility syndrome/Ehlers–Danlos syndrome, hypermobility type (JHS/EDS-HT) commonly suffer from pain. How this hereditary connective tissue disorder causes pain remains unclear although previous studies suggested it shares similar mechanisms with neuropathic pain and fibromyalgia. In this prospective study seeking information on the mechanisms underlying pain in patients with JHS/EDS-HT, we enrolled 27 consecutive patients with this connective tissue disorder. Patients underwent a detailed clinical examination, including the neuropathic pain questionnaire DN4 and the fibromyalgia rapid screening tool. As quantitative sensory testing methods, we included thermal-pain perceptive thresholds and the wind-up ratio and recorded a standard nerve conduction study to assess non-nociceptive fibres and laser-evoked potentials, assessing nociceptive fibres. Clinical examination and diagnostic tests disclosed no somatosensory nervous system damage. Conversely, most patients suffered from widespread pain, the fibromyalgia rapid screening tool elicited positive findings, and quantitative sensory testing showed lowered cold and heat pain thresholds and an increased wind-up ratio. While the lack of somatosensory nervous system damage is incompatible with neuropathic pain as the mechanism underlying pain in JHS/EDS-HT, the lowered cold and heat pain thresholds and increased wind-up ratio imply that pain in JHS/EDS-HT might arise through central sensitization. Hence, this connective tissue disorder and fibromyalgia share similar pain mechanisms. WHAT DOES THIS STUDY ADD?: In patients with JHS/EDS-HT, the persistent nociceptive input due to joint abnormalities probably triggers central sensitization in the dorsal horn neurons and causes widespread pain.